Draft genome and description of Chryseobacterium manosquense strain Marseille-Q2069T sp. nov., a new bacterium isolated from human healthy skin. (November 2020) - Boxberger, M.; Ben Khedher, M.; Magnien, S.; Cassir, N.; La Scola, B.
Abstract: In 2019, by culturing a skin swab from the hand of a 35-year-old healthy woman using culturomics methods, we isolated the new bacterial strain Marseille-Q2069 T  = CSUR-Q2069. Matrix-assisted desorption/ionization time-of-flight mass spectrometry failed to identify this isolate. Analysis of the 16S rRNA gene and Genome-to-Genome comparison suggested that this taxon belongs to a novel bacterial species within the family Flavobacteriaceae in the phylum Bacteroidetes . We described here the main phenotypic characteristics, genome sequence and annotation of Chryseobacterium manosquense strain Marseille-Q2069 T, a new member of the Chryseobacterium genus, that we propose as type strain.